Assigning resistivity values to rock quality designation indices using integrated unmanned aerial vehicle and 2D electrical resistivity tomography in granitic rock - Muhammad Junaid; Rini Asnida Abdullah; Kamal Abdelrahman; Arshad Ullah; Sajid Mahmood; Radzuan Sa'ari; Amber Islam (Geocarto International)
Rock quality designation (RQD) is a standard technique in mining and geotechnical investigation for quantifying the quality and degree of jointing of the rock mass. However, the need for expeditious and inexpensive geotechnical site characterization is the prime motivation for modifying RQD. This research work integrates 2D Electrical Resistivity Tomography (2D ERT) and Unmanned Aerial Vehicle (UAV) conducted at Site 1 and Site 2. The UAV survey was performed to calculate RQD on the rock surface using volumetric Joint Counts (Jv) at Sites 1 and 2. A 2D ERT survey was conducted to obtain the corresponding subsurface resistivity values. Using k-nearest neighbours (k-NN), resistivity values were assigned to various RQD indices such as very poor rocks (<350 Ωm), poor rock (350–1150 Ωm), fair rock (1150–1850 Ωm), good rock (1850–2500 Ωm) and >2500 Ωm excellent rock. Based on the established correlation of RQD and resistivity, the subsurface rock mass quality at Site 1 was predominantly good and excellent rock, while at Site 2, poor rock was significantly reported. This research concluded that rock mass characterization using RQD is more rapid and inexpensive than the direct or indirect calculation of RQD. The combined 2D ERT and UAV deployed in this research study provide an environmentally non-destructive approach for slope stability assessment.